Taṭwīr al-Kitāb al-Madrasī “Buku Pembelajaran Bahasa Arab Kelas V Kurikulum 2013” Bi al-Wasā’il as-Sam`iyyah al-Baṣariyyah `Alā Fahm al-Qawa`id an-Naḥwiyyah Bi al-Madrasah al-Ibtidāiyyah al-Islāmiyyah al-Ahliyyah Cendekia Darussalam - Rauzatun Nufus; Buhori Muslim (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2021)
Textbooks are the main media used by teachers and students in the instructional process. Therefore, the Qawa'id Nahwiyah learning book which is unstructured, general, and not equipped with various examples, will make students feel bored and do not understand about the qawaid nahwu. In this study, the researcher was developing an Arabic learning book for grade five in the 2013 curriculum by using audio-visual media. This research was designed to find out how to develop Arabic learning books for grade five in the 2013 curriculum using audio-visual media and how to determine the effectiveness of Arabic learning books for grade five in the 2013 curriculum by using audio-visual media. Furthermore, the Research and Development model by Borg and Gall was used in this study as a research method. Data collection consisted of interviews, questionnaires, and tests. In addition, the participants in this study were 280 students as population, and the students in all grades five consisting of 25 students were taken as samples. according to the results, the researcher found that book development has been carried out through 10 stages: Potential and problems, gathering information, product design, and design validation in this the value of the first expert was 78 % and the second expert was 77 % it showed that this bool agrees to be used learning Qawa'id Nahwiyah, design improvement, product testing, product revision, usage testing, product revision, and mass product manufacturing. meanwhile, the results of the effectiveness test using the t-test showed that the t count was greater than the t table, namely 4.1 based on a significance level of 5% 2.06 and 1% 2.80.